Impact of body composition and nutritional status on health outcomes in adultcystic fibrosis patients - KOCAKAYA, DERYA; OLGUN YILDIZELİ, ŞEHNAZ; ERYÜKSEL, SEMİHA EMEL; CEYHAN, BERRİN (My University, 2019)
AIM: Cystic fibrosis (CF) is a multi-systemic disease. Chronic inflammation and malabsorption may affect body composition, respiratory function and health outcomes. Our aim was to examine anthropometric measures, microbiologic data, spirometric data, comorbidities and how body composition may impact health outcomes in adult CF patients. METHODS: 31 adult CF patients (15 female, 16 male) with mean age 25 (18-42) and 23 controls were enrolled. The modified Medical Research Council (mMRC) scale, 6 minute-walk-test and pulmonary function test were performed. Anthropometric data including body mass index (BMI), fat-free mass index (FFMI) and total body fat percentiles were measured. Clinical indices, presence/absence of pancreatic insufficiency and method of nutrition were recorded. RESULTS: Mean duration of disease was 18.6±7.5 years. 24 of the patients (77%) were below targeted BMI. Mean BMI of the patients was 20.6±3.1 kg/m2 and mean FFMI was 16.4±1.6 kg/m2. When compared to control group, both BMI and FFMI were lower in CF patients (p<0.05 and 0.00) and both were correlated with age ( p: 0.008, r: 0.468 and p: 0.036, r:0.377). Female patients had lower FFMI (15.7±1.3 vs17.1±1.6, p:0.01) and higher fat percentile (22.7% vs 12.5%, p:0.00) than male patients. FFMI was found to be positively correlated with FEV1L and FVC L (p:0.017, r: 0.025 and p:0.05 and r: 0.490, respectively). 20 patients (65%) had pancreatic insufficiency and all were under pancreatic enzyme replacement medication. This group of patients had lower fat percentile then the group without pancreatic insufficiency (15.0±6.7% vs 23.2±9.0%; p:0.011) 16 patients (52%) had anemia and FFMI positively correlated with hemoglobin values (p:0.03, r: 0.390). 17 patients (55%) were receiving oral nutritional support and these patients had lower BMI then those who were not receiving (19.4±2.6 vs 22.1±2.9, p: 0.013). CONCLUSION: The prevalence of malnutrition was high in adult CF patients and lung function is correlated with nutritional status. Periodic measurement of anthropometrics and close monitoring of nutritional status may improve respiratory function and health outcomes in adult CF patients